Detection of the Dimorphic Phases of Mucor circinelloides in Blood Cultures from an Immunosuppressed Female. (29th September 2016) - Arroyo, Miguel A.; Schmitt, Bryan H.; Davis, Thomas E.; Relich, Ryan F.
Abstract : Mucormycosis fungemia is rarely documented since blood cultures are nearly always negative. We describe a case of Mucor circinelloides fungemia in a patient with a history of a sinus infection, sarcoidosis, and IgG deficiency. The identity of the isolate was supported by its microscopic morphology and its ability to convert into yeast forms under anaerobic conditions. The early detection, initiation of liposomal amphotericin B treatment, and reversal of underlying predisposing risk factors resulted in a good outcome.